ERMON (ACCHIK SHUVOK) NING PHARMACOLOGICAL PROPERTIES AND VETERINARY SIGNIFICANCE - Allanazarov Ghiyas Shokirjonovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information on the technology of obtaining a liquid extract and the composition and effects of bitter wormwood.